Machine learning in non-stationary environments introduction to covariate shift adaptation - Sugiyama, Masashi, 1974- (MIT Press, 2012)
This volume focuses on a specific non-stationary environment known as covariate shift, in which the distributions of inputs (queries) changes but the conditional distributions of outputs (answers) is unchanged, and presents machine learning theory algorithms, and applications to overcome this variety of non-stationarity.
Keywords: Machine learning.; elektronické knihy; electronic books